Mechanical and thermal properties of thermoplastic polyurethane reinforced with roselle and sugar palm hybrid composites - Ali, Mohd Radzi (2019)
Recently, with the increasing environmental concerns of many researchers conduct various research activities and efforts to address environmental issues by replacing the conventional fibres (synthetic fibres) to natural fibres as more environmentally friendly in polymer composites. The advantages of natural fibres in polymer composites are low cost, light weight, biodegradable and have good mechanical properties. In Malaysia, there are about 800-1200 hectare roselle trees that have been planted. With the size of this plantation, dumping cut trees will cause problems for farmers for disposal. The easiest way to dispose for them is to do open burning. The disposal of roselle trees will cause the effects of natural pollution. Therefore, roselle trees are selected for use in composites to reduce environmental problems. Additional, this research focuses on roselle and sugar palm plant to produce hybrid composites. Hybridization two types of natural fibres due to RF has high tensile strength and low fibre cost. SPF has good mechanical properties especially in terms of impact. These two criteria are combined to further enhance the mechanical and thermal properties of TPU composites. In additional, this research aims on capability performances and sustainability of roselle and sugar palm fibre as the reinforcement materials for polymer hybrid composites. Hence, several modifications were carried out to improve the mechanical and thermal properties of RF and SPF reinforced thermoplastic polyurethane hybrid composites. The purposes of this research consist of four parts. In the first part, roselle fibre (RF)/reinforced thermoplastic polyurethane (TPU) composites were prepared with different fibre sizes i.e. 125 μm and lower, 125–300 and 300–425 μm using the internal mixer and hot compression. The finding shows that mechanical properties were improved with increasing of the fibre sizes. The thermal properties were improved as the fibre size increased. The second part, the influence of fibre varying contents (0 – 50 wt. %) on the mechanical and thermal stability of RF/TPU composites were investigated. From the results, the effects of fibre contents show improved in tensile, flexural and impact test. Besides that, the thermal properties of RF/TPU composites with different fibre contents had improved the thermal stability. The third part, the effects of hybridization of RF/sugar palm fibre (SPF)/TPU composites. Hybridization of RF/ SPF at weight ratio 75:25, 50:50, and 25:75 were performed using hot compression. Obtained results indicated that hybridization of RF/SPF/TPU hybrid composites increased the impact strength with increasing of sugar palm fibre contents. Otherwise, it gave effects on reduction of the tensile and flexural properties. In addition, the thermal properties of RF/SPF/TPU hybrid composites were improved following with incorporation of sugar palm fibres. Finally, the effect of surface treatment RF/SPF/TPU hybrid composites on mechanical and thermal properties. Roselle and sugar palm fibres are treated with alkalization agent. From the results, the treated RF/SPF/TPU hybrid polyurethane composites fibres shows increased in the mechanical properties of TPU composites compared to untreated. The highest tensile is 14.26 MPa, flexural strength is 14.05 MPa and impact strength is 23.76 kJ/m² was obtained from treatment 6 % NaOH concentration on RF/SPF hybrid composites. Physical properties showed lower water uptake of the treated thermoplastic polyurethane hybrid composites. The lowest water uptake is 7.97 % and thickness swelling is 6.49 % obtained from 9 % NaOH concentration after soaked in water for 7 days. The thermal properties also improved the thermal stability. Overall, RF/SPF/TPU hybrid composites have the potential to be an alternative material in polymer composites products to compete with the conventional fibres. Besides, it can reduce the problem of dumping and open burning on the environment. In addition, this hybrid composite can be applied to the automotive parts especially as a battery holder and liner.